2012
DOI: 10.1124/dmd.111.040329
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Identification of MicroRNAs That Regulate Hepatic Nuclear Factor 4α Expression

Abstract: ABSTRACT:Hepatic nuclear factor 4␣ (HNF4A) is a nuclear transcription factor that regulates the expression of many genes involved in drug disposition. To identify additional molecular mechanisms that regulate HNF4A, we identified microRNAs (miRNAs) that target HNF4A expression. In silico analyses suggested that HNF4A is targeted by many miRNAs. We conducted in vitro studies to validate several of these predictions. With use of an HNF4A 3-untranslated region (UTR) luciferase reporter assay, five of six miRNAs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 39 publications
2
65
0
1
Order By: Relevance
“…In contrast, a clinical study in Han Chinese did not show an association of miR-148a expression with CYP3A4 protein expression (Wei et al, 2013). Multiple different miRNAs target hepatic nuclear factor 4a (HNF4A), a master regulator of many drug-disposition genes that may also be a key contributor to P450 gene expression (Takagi et al, 2010;Ramamoorthy et al, 2012;Wang and Burke, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a clinical study in Han Chinese did not show an association of miR-148a expression with CYP3A4 protein expression (Wei et al, 2013). Multiple different miRNAs target hepatic nuclear factor 4a (HNF4A), a master regulator of many drug-disposition genes that may also be a key contributor to P450 gene expression (Takagi et al, 2010;Ramamoorthy et al, 2012;Wang and Burke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are at least 38 genetic polymorphisms in the P450 genes that are predicted to either create or destroy miRNA binding sites (Ramamoorthy et al, 2012). A single-nucleotide polymorphism in the miR-34a binding site of the HNF4A gene (rs11574744) alters the targeting of that gene by miR-34a (Ramamoorthy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…HNF-4α is required for the development of the liver and it is known as a "master regulator" that regulates the expression of many genes. 16) HNF-4α has been reported to modulate CYP expression in the liver by interacting with xenosensor receptors (e.g. PXR and CAR), glucocorticoid receptors, feeding-fasting cycle target PGC-1α, sexual-dimorphism factor Stat5b, and other liver-enriched factors, such as C/EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Rifampin-induced miRNA expression changes are correlated with rifampin treatment changes in PXR and P450 [6,[10][11][12]. MiRNA can indirectly influence rifampin-induced drug deposition through gene regulation [11,[13][14][15]. Proteins are synthesized from mRNA templates through a highly conserved process, many studies have reported that the functions of miRNAs can be understood by analyzing miRNAs-regulated mRNA-related PIN [16][17][18].…”
Section: Introductionmentioning
confidence: 99%